PENGARUH REBRANDING, KERAGAMAN PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MAKO CAKE & BAKERY DI MARGONDA DEPOK - Reynaldi, Reynaldi; Karla, Eva; Stevianus, Stevianus (Journal of Information System, Applied, Management, Accounting and Research; Vol 9 No 2 (2025): JISAMAR (March-May 2025), 2025)
The purpose of this study was to analyze the effect of rebranding, product diversity and price perception on purchasing decisions at Mako Cake & Bakery in Margonda Depok. The analysis method in this study used quantitative primary data, the test stages carried out were: normality test, multicollinearity test, heteroscedasticity test, T test, F test, and coefficient of determination. The data used in this study used a questionnaire instrument and valid data that was successfully collected as many as 100 respondents. The data collection technique used in this study was through a questionnaire. The testing tool used was SPSS software version 25. The results of the study showed that partially the Rebranding variable (X1) with a sig value of 0.000 <0.05, Product Diversity (X2) with a sig value of 0.005 <0.05. and price perception with a sig value of 0.000 <0.05 This means that partially Rebranding, Product Diversity and Price Perception have a positive and significant effect on Purchasing Decisions. Meanwhile, the simultaneous calculation obtained a sig value of 0.000 <0.05. This means that Rebranding, Product Diversity and Price Perception together (simultaneously) have a positive effect on Purchasing Decisions at Mako Cake & Bakery.